2012
DOI: 10.1108/14601061211243657
|View full text |Cite
|
Sign up to set email alerts
|

The ethical culture of organisations and organisational innovativeness

Abstract: Purpose: The purpose of this article is to examine the relationship between the ethical culture of organisations and organisational innovativeness. Methodology:A quantitative empirical analysis was conducted on the basis of a survey of 147 respondents within the public sector in Finland. A multivariate linear regression analysis was done to examine how the ethical culture of organisations is related to organisational innovativeness.Findings: A positive link was found in the ethical culture of an organisation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 59 publications
6
60
0
5
Order By: Relevance
“…This finding supports the idea that the ethical culture of an organisation promotes ethical behaviour. Riivari et al (2012) investigated the role of ethical culture on organisational innovativeness in a pilot study and found that the two are linked. Huhtala et al (2011) investigated the role of ethical culture in the occupational well-being of managers and found that ethical culture is positively associated with managers' work engagement.…”
Section: Ethical Culture Of Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the idea that the ethical culture of an organisation promotes ethical behaviour. Riivari et al (2012) investigated the role of ethical culture on organisational innovativeness in a pilot study and found that the two are linked. Huhtala et al (2011) investigated the role of ethical culture in the occupational well-being of managers and found that ethical culture is positively associated with managers' work engagement.…”
Section: Ethical Culture Of Organisationsmentioning
confidence: 99%
“…Finally, Riivari et al (2012) investigated the relationship between the ethical culture of an organisation and innovativeness. Their study indicated that there might be a link between the two.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, our study lends cross-cultural support to the research in Finland on the impact of ethical organisational culture on organisational innovativeness (Riivari and Lämsä, 2014;Riivari et al, 2012). Moreover, it indicates the crucial importance of congruency of management, discussability and clarity for enhancing a public organisation's capability to innovate, in particular, at behaviour and process levels in both socio-cultural contexts.…”
Section: Discussionmentioning
confidence: 97%
“…This gap has been addressed in recent studies by Riivari et al (2012), Riivari and Lämsä (2014), who have found a positive interrelation between ethical organisational culture and organisational innovativeness. Their studies were carried out in the Finnish society, which is strongly dominated by values of accountability, equality, trustworthiness, honesty and justice (Helkama and Seppälä, 2006;Lämsä and Viljanen, 2014).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation